Modelo de perfil de gestor público: um estudo de caso na UFMG - Teixeira, Letícia Magalhães Munaier (2019)
The main goal of this work is to develop, from a case study that took place at the Federal University de Minas Gerais (UFMG), a reference model for the professional profile for the function of Administrative Superintendent of academic unities of UFMG. Analyzing the function of Administrative Superintendent of academic unities of UFMG, this work intends to develop a reference model for the professional profile for this function, from specific literature, from research made through the application of online and anonymous questionnaires with the occupants of this function at UFMG, such as their immediate bosses, the directors of their academic unities, and from personal semi-structured interviews. From this research of qualitative nature about one aspect of the academic management in UFMG, it intends, yet, to forward improvements proposals for the management, in addition to providing subsides for politics of human resources of UFMG. The results demonstrated which are the characteristics of the reference model for the professional profile that a manager must have to act as an Administrative Superintendent of academic unities of UFMG, discriminating abilities, knowledge and values that he must possess. The attributions of the function of Administrative Superintendent at UFMG were also raised and it was identified the facilitative aspects and restrictions of its acting, such as its target audience or the recipients of the services of the Administrative Superintendent.